Inspector Logan - Richard MacAndrew (UK Cambridge University Press, 2002)
A missing woman and a dead body welcome Inspector Jenny Logan to her new job with the Edinburgh police. Logan questions the husband of the dead woman and a local doctor about the murder, but can she believe what they say? Then, a piece of jewellery leads Logan to the killer.